A Comparison of Plasma Efavirenz and Tenofovir, Dried Blood Spot Tenofovir-Diphosphate, and Self-Reported Adherence to Predict Virologic Suppression Among South African Women. (1st July 2019) - Phillips, Tamsin K.; Sinxadi, Phumla; Abrams, Elaine J.; Zerbe, Allison; Orrell, Catherine; Hu, Nai-Chung; Brittain, Kirsty; Gomba, Yolanda; Norman, Jennifer; Wiesner, Lubbe; Myer, Landon; Maartens, Gary
Abstract : Background: Tenofovir-diphosphate (TFV-DP) in dried blood spots (DBS) is an objective long-term adherence measure, but data are limited on its ability to predict virologic suppression (VS) in people on antiretroviral (ARV) treatment. There are also no data comparing DBS TFV-DP with plasma ARV concentrations as predictors of VS. Methods: Women who were on a first-line regimen of tenofovir, emtricitabine, and efavirenz (EFV) were enrolled in a cross-sectional study. Plasma EFV and tenofovir (TFV), DBS TFV-DP assays, and 30-day self-reported adherence were evaluated as predictors of VS (<50 copies/mL) with the area under the curve of receiver operating characteristics and logistic regression. Results: We enrolled 137 women; mean age of 33 years; median 4 years on antiretroviral therapy; 88 (64%) had VS. In receiver operating characteristics analyses: DBS TFV-DP [0.926 (95% CI: 0.876 to 0.976)] had a higher area under the curve than plasma TFV [0.864 (0.797 to 0.932); P = 0.006], whereas plasma EFV [0.903 (0.839–0.967)] was not significantly different from DBS TFV-DP ( P = 0.138) or plasma TFV ( P = 0.140); all ARV assays performed better than self-report. The association of TFV-DP in DBS with VS strengthened with increasing concentrations [reference <350 fmol/punch: 350–699 fmol/punch aOR 37 (8–178); 700–1249 fmol/punch aOR 47 (13–175); ≥1250 fmol/punch aOR 175 (20–1539)]. "White coat adherence" (defined as DBS TFV-DP <350 fmol/punch with detectable plasma TFV) was only detected in 4 women. Conclusions: Plasma EFV, TFV, and DBS TFV-DP were all strong predictors of VS. EFV or TFV assays have potential for development as point-of-care assays for use as objective adherence measures in resource-limited settings. Abstract : Supplemental Digital Content is Available in the Text.